Mudanças no mundo dos trabalhadores: um estudo sobre as vendedoras de produtos por catálogo Avon e Natura - Lima, Cíntia Fiorotti (2009)
This scientific work argues the process of changes in the world of the work in the present time from the experiences lived deeply for the saleswomen of products of Avon and the Natura. The research of training sources such as manual, catalogues, news and codes of behavior produced by these companies, made possible to identify the form with that the involved force of work in the sales for catalogues is organized. The analysis of this material also allowed to understand the used mechanisms to convince these salesmen to fulfill the goals of sales. However, dialoguing with the stories of these workers, one became evident the tensions and conflicts between the practical ones intended by the companies and the practical ones effectively materialize by the saleswomen. In this context, the disputes around the meaning of this work had questioned the vision defended for the companies who define such independent occupation as, attributing denominations to it as peddlers or consultants with the purpose to deprive of characteristics any type of work relation and employment bond. Therefore, I looked for in such a way to analyze the changes in the world of the workers from these conflicts and tensions, valuing the subjectivity of the workers who live deeply this process, as the changes lived throughout the process of capitalist accumulation